2018
DOI: 10.1371/journal.pone.0204213
|View full text |Cite
|
Sign up to set email alerts
|

The structural equation model on self-efficacy during post-op rehabilitation among non-small cell lung cancer patients

Abstract: BackgroundsSelf-efficacy plays an important role in pulmonary rehabilitation, but it is still unknown which factors exert their effects on postsurgical rehabilitation self-efficacy among non-small cell lung cancer (NSCLC) patients. This study aims to assess relationships among physical function, social factors, psychological factors, quality of life (QOL) and self-efficacy, and the effects of these variables on self-efficacy among NSCLC patients.MethodsA cross-sectional survey was administered to 238 postsurgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…Social support has previously been shown to predict posttraumatic growth (McDonough et al, 2014), and our results verified that social support had positive direct and indirect effects on posttraumatic growth through multiple mediations. The direct relationship between social support and posttraumatic growth has been previously reported in studies of Chinese lung cancer patients (Huang et al, 2018). Recent findings of a Chinese American breast cancer survivor study suggested that social support may facilitate PTG through direct and indirect effect, which is consist with our findings (Yeung & Lu, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…Social support has previously been shown to predict posttraumatic growth (McDonough et al, 2014), and our results verified that social support had positive direct and indirect effects on posttraumatic growth through multiple mediations. The direct relationship between social support and posttraumatic growth has been previously reported in studies of Chinese lung cancer patients (Huang et al, 2018). Recent findings of a Chinese American breast cancer survivor study suggested that social support may facilitate PTG through direct and indirect effect, which is consist with our findings (Yeung & Lu, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…Although social support did not differ between SL and L patients at baseline, more perceived social support was a significant factor for all QoL measures used in this report. The literature indicates that social support as well as psychosocial and behavioral supportive interventions can have positive impact on post-surgical QoL (31,32). Thus, future research should consider whether social support could potentially be an effect modifier of the impact of extent of surgery so that the impact on QoL of more invasive surgery could be attenuated by increased social support.…”
Section: Discussionmentioning
confidence: 99%
“…12 Social support has been proven to have a positive impact on the health, mental and cognitive wellbeing and quality of life of the patient and his/her caregiver. [13][14][15] In addition, social support is a significant factor in protecting against negative mental states, reducing unpredictable behaviour and mortality. [16][17][18][19][20] Social support influences quality of life through two psychological mechanisms: behavioural processes (eg prohealth behaviour, adherence) and psychological processes (stress appraisal).…”
Section: Social Supportmentioning
confidence: 99%
“… 12 Social support has been proven to have a positive impact on the health, mental and cognitive well-being and quality of life of the patient and his/her caregiver. 13–15 In addition, social support is a significant factor in protecting against negative mental states, reducing unpredictable behaviour and mortality. 16–20 …”
Section: Introductionmentioning
confidence: 99%